Challenges faced by schools in the implementation of inclusive education: a case study of Muzvezve cluster in Mhondoro- Ngezi District - Makamba, Marian (Midlands State University, 2017)
The study aimed at investigating the challenges faced by schools in implementing inclusive education in three secondary schools in Mhondoro- Ngezi District and identifying their effects on the teaching and learning process. It also highlighted possible solutions to the problems. The researcher utilized the descriptive survey method. In this study, thirty teachers made up the sample, three focus group interviews were carried out and direct observations were carried out in each of the three schools. The questionnaire, focus group interview schedule and direct observation guide were used as research instruments in the study. The data was presented and analysed thematically using the research questions. The study revealed that the challenges faced by schools in implementing inclusive education include lack of appropriate skills on the part of the teachers, lack of clear cut policy and planning on inclusive education, inappropriate infrastructure and lack of funding, discrimination and stigmatization among teachers, learners and the community, large teacher-pupil ratio and prohibitive teaching loads, poor dissemination of information, lack of team work and collaboration and lack of motivation on the part of the teacher and learner. It has been established through the study that these problems result in inappropriate teaching strategies, divided and unbalanced attention to learners, stigmatization and low self-esteem among learners, high dropout rate and poor learners’ performance. The study also revealed that the possible solutions are; provision of appropriate and relevant training to teachers, provision of relevant and appropriate infrastructure, provision of enough funding, lowering teacher-pupil ratio and teaching loads, government to design a policy to enhance effective inclusion, supervision and monitoring of schools and provision of psychological and social welfare services to give professional evaluations and advice.